Short-term CD4 cell response after highly active antiretroviral therapy initiated at different times from seroconversion in 1,500 seroconverters. - Babiker, A; Darbyshire, J; Pezzotti, P; Porter, K; Prins, M; Sabin, C; Walker, A (2003)
The effect of HIV infection duration and CD4 cell count on short-term CD4 response was evaluated in treatment-naive seroconverters using logistic regression adjusted for CD4 count before highly active antiretroviral therapy (HAART) as well as for exposure category, age, sex, acute infection, and cohort. This association was also investigated in pretreated seroconverters, further adjusting for prior therapy. CD4 response (increase of >100 cells/microL at 6 months) was more likely if HAART was initiated in the first year following seroconversion (OR = 1.50 [95% CI: 1.07-2.10] compared with 2-5 years). There was no improvement in response from initiating HAART with CD4 count >350 cells/microL compared with 201 to 350 cells/microL. Below 200 cells/microL, however, the chance of a CD4 response appeared to be reduced (OR = 0.72 [95% CI: 0.40-1.28] for 0-200 cells/microL compared with 201-350 cells/microL, P = 0.26). Results were similar for pretreated individuals. Further, in pretreated individuals, a CD4 response was less likely if the CD4 nadir was lower than the pre-HAART CD4 count (OR = 0.18 [95% CI: 0.10-0.36] for >150 cells/microL difference between nadir and pre-HAART CD4 count vs. no difference, P < 0.001). Given the limitations of observational studies, particularly the inability to control for unmeasured confounders, these findings suggest that the initiation of HAART within the first year following seroconversion appears to improve short-term immunologic response. After that time, there is little to be gained in terms of short-term response from initiating HAART before reaching a CD4 count of 200 cells/microL.